An Exploratory Study of the Ethnophysics Concept in the Spiritual Dance of Mpaa Toja-Kalero Donggo to Identify Physics Learning Content as a Learning Resource - Agustinasari, Agustinasari; Fiqry*, Rizalul (Universitas Syiah Kuala, 2023)
Ethnophysics discusses the interaction between culture and physics concepts utilized as learning resources. The use of resources close to the environment fosters contextual learning and can help students develop critical thinking skills. This research assesses physics concepts in the traditional dance of Mpa'a Toja-Kalero Donggo. The research goal is to identify physics content that can be used as a learning resource. The research is descriptive-qualitative, using the content analysis method. The object of research is the Mpa'a Toja-Kalero video, documentation of Majelis Kebudayaan Mbojo (Makembo), which was determined through purposive sampling. Methods of data collection include observation and literature review. The observation method is used to examine the various elements of mpa'a Toja-Kalero, such as the music and dance moves. Meanwhile, the literature review focused on analyzing the physics concepts in the spiritual dance Mpa'a Toja-Kalero. According to the findings of the analysis, Mpa'a Toja-Kalero contains physics concepts such as sound waves, regular straight motion, centripetal force, air resistance, center of mass, moment of inertia, and downward vertical motion